Influence live streaming TikTok to purchase intention of skincare products in Indonesia - Rajagukguk, Nova Winda; Suwarno, Wulan; Anggraeni, Adilla (Institute of Advanced Engineering and Science, 2024)
TikTok Live Streaming accommodates the needs of sellers to be able to communicate two-way between sellers and buyers. A new type of online business called live streaming allows users to watch and make purchases. The host is the person who sells the goods during the live-streaming event, and the live streaming platform is the location where the live-streaming takes place. The purpose of this study is to further understand the factors that determine customer purchase intention through tiktok live streaming using the IAM model. In previous research, several variables in the IAM model have a positive correlation with purchase intention. This study aims to see the impact of adding one variable, namely perceived persuasiveness within the framework of the IAM model on purchase intention. This research aims to see the impact of adding one variable, perceived persuasiveness in IAM model framework on purchase intention. This study using the quantitative method was employed using partial least square structural equation modeling (PLSSEM). The SmartPLS 4.0 software was applied to examine the proposed model.